Grafting a mesomorphic Schiff base onto gold nanoparticle via ester link – photoluminescence, mesomorphism, electrical conductivity and antioxidant activity. Issue 4 (16th March 2019) - Das, Nirmalendu; Borah, Debasish; Acharya, Himadri; Choudhury, Sudip; Prasad, S. Krishna; Rao, D.S. Shankar; Bhattacharjee, Chira R.
ABSTRACT: Liquid crystal-gold nanoparticle (GNP-LC) composite were accessed via covalent coupling of 4-mercaptophenol capped gold nanoparticles (GNP) and a carboxylic acid functionalised rod shaped mesomorphic Schiff base (LC). The Schiff base ligand and the composite both showed schlieren texture with distinct difference in phase transition temperature. The X-ray diffraction study suggested a smectic C mesophase for the compounds. The LC and GNP-LC, both exhibited room temperature photoluminescence when excited at 264nm.The transmission electron micrography revealed the composite to be nearly monodisphersed having almost spherical shape of 2nm size. The composite material in addition to being mesomorphic exhibited pronounced AC conductivity in the semiconductor domain and antioxidant activity. Graphical Abstract: